2007
DOI: 10.1089/gte.2007.0001
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes of Families Affected by Adrenoleukodystrophy toward Prenatal Diagnosis, Presymptomatic and Carrier Testing, and Newborn Screening

Abstract: Families affected by adrenoleukodystrophy (ALD) and adrenomyeloneuropathy (AMN) were surveyed to elicit attitudes toward prenatal, presymptomatic and carrier testing, and newborn screening in order to determine the level of support that these families have for current and future genetic testing protocols. Identifying attitudes toward genetic testing, including newborn screening, is especially important because of new data regarding therapeutic options and the possible addition of ALD to newborn screening regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
1
13
0
Order By: Relevance
“…These findings are consistent with previous studies in which pregnancy outcomes for these conditions have been assessed. [14][15][16][17][18][19][20] A key finding was that the women in this study were overwhelmingly positive about their experiences of NIPD. Furthermore, the information they received from health professionals was considered to be adequate and provided an overview of key issues.…”
Section: Discussionmentioning
confidence: 67%
“…These findings are consistent with previous studies in which pregnancy outcomes for these conditions have been assessed. [14][15][16][17][18][19][20] A key finding was that the women in this study were overwhelmingly positive about their experiences of NIPD. Furthermore, the information they received from health professionals was considered to be adequate and provided an overview of key issues.…”
Section: Discussionmentioning
confidence: 67%
“…Ten of the quantitative studies were of questionable validity. Six of these studies either reported no evidence of reliability or validity of survey instruments used (Finlay et al., 2008; Schaller, Moser, Begleiter, & Edwards, 2007; Segal, Polansky, & Sankar, 2007; van Korlaar et al., 2005), created scales for use in the study but did not report their psychometric characteristics (Nyrhinen, Hietala, Puukka, & Leino‐Kilpi, 2007), or used scales with low reliability (Bowen, Bourcier, Press, Lewis, & Burke, 2004). One of the 10 studies was compromised by using a historical cohort to provide outcome measures (Suthers, Armstrong, McCormack, & Trott, 2006); one was based on showing future lawyers and physicians a single emotion‐laden video to elicit attitudes toward genetic testing (Elger & Harding, 2006); and one limited the survey to individuals with working telephones (Rose, Peters, Shea, & Armstrong, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…This finding is consistent with other research showing that, for the most part, parents want genetic and health information that has any bearing on the well-being of their children. 31-33 Studies of families of children with other conditions vary in the extent to which the availability of a known condition-specific treatment affects parent opinions. 34-36 But consistent with most of these studies, many parents of children with FXS felt that earlier identification would enable access to early intervention and therapy services, even though those services are not FXS specific and their efficacy with FXS has not been demonstrated.…”
Section: Discussionmentioning
confidence: 99%